Creative rewritings of critical texts: report on a creative workshop, 3rd December 2022 - Helen E. MUNDLER-ARANTES; Laure-Hélène ANTHONY-GERROLDT; Florent DA SYLVA; Heathir LAWRENCE-MONASSA; Tanya TROMBLE-GIRAUD; Sara GREAVES (E-REA)
This article is a report on a creative writing workshop held at Aix-Marseille University under the auspices of LERMA on 3rd December 2022, and led by Helen E. Mundler. The aim of the workshop was to celebrate the twentieth anniversary of e-Rea by using the cut-up method, popularized in the 1960s by William Burroughs, to recycle articles taken from issues of this review that have been published over the last two decades. The first part of the article is a critical introduction by Helen E. Mundler in which she explains the rationale behind the workshop. Building on her article on creative and critical convergence published in e-Rea 20.1,1 she relates cut-ups to other types of recycling texts, such as quotation, ventriloquy, pastiche and parody, with particular reference to the work of A.S. Byatt, in whose 1996 novel, Babel Tower, the technique features. The theoretical underpinnings of cut-ups are explained, their capacity to generate new meaning examined, and the question of whether and how to take control of the text thus produced, rather than to leave it to chance, is touched upon. In the second part of the article, each of the participants provides a brief commentary on their production in response to the intentionally broad question, “How does your creative output relate to your research?”